More Funding, More Insecurity: The Paradox of the Fight against Violent Conflict, Insecurity and Corruption in Nigeria - Prince EZE (Covenant University Journal of Politics and International Affairs, 2023)
Against the background to address violent conflict and rising insecurity that have bedeviled the Nigerian State, this paper, using primary and secondary data and the Marxist Political Economy Approach as a framework for analysis, examined how corruption in Nigerian system has contributed to and hindered the fight against insecurity. The findings of the study revealed that in the last 6-7 years, budgetary provisions to fight violent conflict and insecurity have significantly increased without a corresponding increase in security. To this end, funds budgeted to fight insecurity are diverted into private hands for personal enrichment and aggrandizement. It is in this regard that it is recommended among other things, that to win the war against corruption and insecurity, priority and consideration must be placed on the fight beyond political statements and conference speeches. Patriotism, dedication, political will, sincerity, integrity, and commitment are needed both on the part of the government, those fighting corruption and insecurity, and the citizens. Beyond these, Government should establish a special court to hear matters of corruption and insecurity, to avoid unnecessary delays that hinder justice from being served at the end of the day.